TELEGRAM BOT USAGE AS AN INSTRUCTIONAL DESIGN METHOD - Ts. Nur Elimtiaz Abidin; Noor Haty Nor Azam; Mohd Azmil Mohd Yusof (International Journal of Accounting, Finance and Business, 2022)
In Malaysia, educational institutions have shifted to online learning in response toMalaysia’s Ministry of Higher Education's current requirement. In response to thisrequirement, there is a sudden surge among academicians in conducting their delivery methodsfor online education purposes; for instance, learning management systems, websites, socialmedia platforms, and collaborative applications such as Microsoft Teams and GoogleClassroom. However, the current method being used is still insufficient as it was hampered byvarious critical disadvantages which discounted its objective effectiveness. Academicians mustnot disregard students with limited internet quotas and low-speed internet connections. To fillthe gap, this paper aims to discuss Telegram Bot usage and its advantages as an instructionaldesign method. Besides, a survey had been conducted on a group of students beforeimplementing Telegram Bot in the whole class. As a result of the students’ feedback, TelegramBot can be used as one of the educational tools which support the teaching and learningprocess.